(untitled) (Bangladesh Journal of Botany, 2014)
In an average, 2106 fungal colony forming units were settled within ten minutes on one square meter area at noon from the air of Dhaka University campus during February 2011 to January 2012. Among the identified fungi, Aspergillus was one of the most dominating genus in all the stations over the study period. The second was Penicillium followed by Cladopsorium, Curvularia, Alternaria, Fusarium, Trichoderma, Pestalotia, Rhizopus and Colletotrichum. In the dry winter (December - February), Alternaria, Cladosporium, Curvularia and Rhizopus showed its peak. Hot humid summer (April) is the most favourable season for the occurrence of Colletotrichum. Similarity has been found in fungal biodiversity in the indoor and outdoor air. However, higher number of colony was recorded from indoor (57.23%) than that of outdoor air. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18029 Bangladesh J. Bot. 42(2): 273-278, 2013 (December)